Potensi Tax Avoidance Atas Implementasi Tax Holiday: Literature Review - Tamba, Fanny Yolan (Indonesian Accounting Research Journal, 2025)
Tax Holiday policy, which aims to attract direct foreign investment (FDI), provides a reduction or exemption from income tax to certain companies. Although this policy has succeeded in increasing the amount of investment, there are indications that the tax incentives can also be utilized instead of the company to avoid taxes, thereby reducing state revenue. By using the research method literature review, researchers will discuss the effect of tax holiday directly on state revenue by increasing the number of foreign investors, the potential for tax avoidance that can arise due to the implementation of tax holiday, and tax authority efforts to be able to make effective and continue to provide efforts Taxation ease of taxation for foreign investors. Therefore, to optimize the benefits of the Tax Holiday policy, the government needs to increase bureaucratic transparency and efficiency, through the integration of OSS, effective supervision, and education to the community.